The Role of Psychological Capital and Job Securities Factors on Shaping Readiness to Change - Emmanuel Taru Guritna; Tri Panca Titis Arbiansyah (Research Synergy Foundation, 2024)
This study investigates the challenges construction sector companies face due to market disruptions and the lack of innovation, with a specific focus on PT Wijaya Karya (WIKA), a leading Indonesian construction firm. Drawing on Kodak's failure as a cautionary example of the risks of neglecting technological advancements, the research underscores the critical need for companies to remain adaptable and ready to innovate to address evolving customer demands. In response to a significant financial loss of IDR 7.13 trillion in 2023, WIKA implemented cost-saving measures, including workforce restructuring and halting recruitment. Despite these setbacks, the company showcased resilience by initiating innovative projects, such as electric motorcycles and precast concrete technologies, contributing to its recovery. The research emphasizes WIKA's initiatives to cultivate employee readiness for change through programs like Wikasatrian and technology skills development. Utilizing a descriptive quantitative approach, the study surveyed 233 managers and directors from government-owned construction firms (BUMN), employing instruments to measure readiness for change, psychological capital, and job security. Data analysis using Structural Equation Modeling (SEM) confirmed that psychological capital plays a critical mediating role between job security and readiness to change. Findings reveal that job security significantly impacts readiness to change, with psychological capital acting as a strong mediator. The study highlights the importance of investing in psychological resources to foster adaptability, particularly in sectors undergoing technological and organizational transformations. The model demonstrated strong validity, with fit indices including GFI (0.90), CFI (0.98), TLI (0.97), NFI (0.97), and RMSEA (0.09), affirming its robustness and providing valuable insights into the public construction sector, an area often underexplored in previous research.